Green Marketing and Consumer Behavior: Environmental Awareness as Mediator - Risma Nurhaini Munte; Elfina Okto Posmaida Damanik; Dermawan Perangin-angin; Dasmaika Apriani Haloho (Global Research Collaboration, 2026)
This study aims to examine the relationship between green marketing and consumer behavior, and to analyze the mediating role of environmental awareness in the context of North Sumatra, Indonesia. A quantitative explanatory design was employed using a cross-sectional survey of 220 consumers with experience purchasing environmentally friendly products. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0, applying bootstrapping with 5,000 resamples. The results indicate that green marketing is positively associated with consumer behavior (β = 0.312, p < 0.001) and environmental awareness (β = 0.648, p < 0.001). Environmental awareness is also significantly associated with consumer behavior (β = 0.421, p < 0.001). Mediation analysis reveals a significant indirect effect (β = 0.273, p < 0.001), indicating partial mediation. The model demonstrates moderate explanatory power (R² = 0.420 for environmental awareness; R² = 0.563 for consumer behavior) and satisfactory predictive relevance (Q² = 0.301; 0.389). This study is based on a cross-sectional design, which limits causal inference. Additionally, the use of self-reported data may introduce common method bias, although collinearity diagnostics indicate acceptable levels. This study contributes to the literature by providing empirical evidence of a dual-path mechanism linking green marketing to consumer behavior through environmental awareness in a regional Indonesian context, which remains underexplored in prior studies.